Investigating ageing behaviours in supercapacitor (cells and modules) using EEC (electrical equivalent circuit) models - Abubakar, Hadiza Ahmad (2017)
This thesis contributes to the reliability and aging studies of supercapacitors for more efficient use in EV/HEV applications. This thesis demonstrates the effect of aging/failure in supercapacitor cells and module cells using accelerated tests employed to expedite the aging process. The tests, as explained below were categorized based on operational and environmental aging factors associated with supercapacitor failure in EV/HEV applications to; • Investigate supercapacitor cell performance at high temperature and constant voltage individual conditions, and also simultaneously (known as calendar test) • Investigate the effect of voltage balancing/equalization circuits on supercapacitor module cells’ performance during constant current cycling tests under certain environmental and electrical factors • Investigate supercapacitor module cells’ cycling performance in a lab-scale designed electrical DC programmable motor load system that emulates supercapacitor operational conditions in an EV/HEV application.